2022
DOI: 10.2147/clep.s347968
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Early Periprosthetic Joint Infection After Total Hip Arthroplasty

Abstract: Purpose To develop a parsimonious risk prediction model for periprosthetic joint infection (PJI) within 90 days after total hip arthroplasty (THA). Patients and Methods We used logistic LASSO regression with bootstrap ranking to develop a risk prediction model for PJI within 90 days based on a Swedish cohort of 88,830 patients with elective THA 2008–2015. The model was externally validated on a Danish cohort with 18,854 patients. Results Inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 51 publications
(48 reference statements)
1
16
0
Order By: Relevance
“…The 10 database-based studies, with a combined population of 1,892609, cover 4 continents (North America, Oceania, Europe, and Asia) and 9 countries (including the USA, Australia, Korea, Sweden, Denmark, Canada, Finland, France, and Norway). In addition, because Bulow [ 11 ] grouped the populations from Sweden and Denmark separately, we conducted the two data sources in this article in separate Table 1 . For Dale.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 10 database-based studies, with a combined population of 1,892609, cover 4 continents (North America, Oceania, Europe, and Asia) and 9 countries (including the USA, Australia, Korea, Sweden, Denmark, Canada, Finland, France, and Norway). In addition, because Bulow [ 11 ] grouped the populations from Sweden and Denmark separately, we conducted the two data sources in this article in separate Table 1 . For Dale.…”
Section: Resultsmentioning
confidence: 99%
“…2 and 3 . Estimates for the medical database-base studies [ 11 15 , 19 – 22 , 26 ] ranged from 0.34 to 2.45% (Fig. 2 ), and the random-effects overall pooled estimated incidence of PJI was 1.05% (95% CI 0.75–1.46%), with very high heterogeneity ( I 2 = 99.6%; heterogeneity test P = 0).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the risk prediction of PJI has been extensively discussed in the literature. A recent prediction model for early PJI, which was applied in Sweden and Denmark, consisted of the parameters diagnosis leading to endoprosthesis insertion, BMI, American Society for Anesthesiologists (ASA) class, sex, age, and the presence of five defined comorbidities [ 21 ]. A large-scale German study found BMI to be an important risk factor for PJI after hip replacement [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the tool was not specifically tailored to infections and would underestimate the risk of SSI when with a predicted probability >0.10. Recently, Bülow et al 11 developed and validated a risk prediction model for periprosthetic joint infection (PJI) within 90 days following total hip arthroplasty (THA), and confirmed its superior discriminatory ability compared to traditional models. Nevertheless, the inflammatory biomarkers with high predictive value for infections were not incorporated and the area under the curve (AUC) <0.7 suggested relatively inadequate accuracy of the model in their study.…”
mentioning
confidence: 99%